An Assessment Framework for the Training of General Practitioners and Specialists Based on EPAs - Gao, Shenshen; Li, Na; Wang, Xinqiong; Yu, Yi; Zhao, Ren; Trigo, Virgínia; Ramalho, Nelson Campos (Frontiers in Public Health, 2022)
Purpose To contribute to solving the imbalance between supply and demand of pediatric medical care in China, activate the linkage between general practitioner and specialists, maximize the role of general practitioner, optimize and integrate medical resources, and ultimately improve medical level and patient satisfaction. Method We opted for a mixed qualitative and quantitative research method. The qualitative research comprehended focus group and interviews conducted with two panel of experts. The quantitative research was conducted to collect data about the applicability of international entrustable professional activities (EPAs) pediatrics standard in the Chinese context by organizing a seminar with a sample of 60 pediatricians. A questionnaire was designed with EPAs and distributed within professional networks. Structural equations modelling and statistical analysis were used to process the data. Results In this study, Medical Service-Groups Model (MSGM) with four levels was successfully established to measure the correlation between specialized and general EPAs. As expected, results showed that specialized EPAs were built on top of general EPAs. There may be the mediating mechanism that general EPAs contribute by the lower level of specialization EPAs. In addition, the levels 1 and 2 were primarily needed to lay the groundwork for levels 3 and 4, and that these higher levels of EPAs were still the most informative for specialized Gastroenterology EPAs. Conclusions The diagnosis and treatment level of primary general practitioners, as the basis of pediatric medical service chain, affected the clinical disposal ability of specialists. The establishment of MSGM provided theoretical basis for the linkage training of general practitioners and specialist physicians.